2004
DOI: 10.2466/pr0.95.5.291-303
|View full text |Cite
|
Sign up to set email alerts
|

The Interpersonal Cognitive Distortions Scale: Development and Psychometric Characteristics

Abstract: In this study, an Interpersonal Cognitive Distortions Scale was developed to assess cognitive distortions in individuals' interpersonal relationships. The sample comprised 425 university students. A factor analysis yielded three factors: Interpersonal Rejection, Unrealistic Relationship Expectation and Interpersonal Misperception. To examine construct validity the correlations between the scores on the Interpersonal Cognitive Distortions Scale and the Automatic Thoughts Scale (.54), the Irrational Belief Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 23 publications
5
17
0
1
Order By: Relevance
“…A study by Hamamci (Hamamci, ) examined whether the CEs ‘mindreading’ (i.e., predicting another's thoughts), ‘arbitrary inference’ (drawing unwarranted conclusions) and ‘overgeneralization’ (taking one piece of evidence and generalising to other situations) were related to marital conflict. CEs were assessed using the Interpersonal Cognitive Distortions Scale (ICDS; Hamamci & Büyüköztürk, ) and were grouped into three categories: (1) Interpersonal Rejection, (2) Unrealistic Expectations and (3) Interpersonal Misperceptions. Results revealed that having CEs pertaining to unrealistic expectations (‘I need a person around me at all times’) in one's partner was associated with high levels of relationship conflict.…”
Section: Interpersonal Behaviour and Depressionsupporting
confidence: 92%
“…A study by Hamamci (Hamamci, ) examined whether the CEs ‘mindreading’ (i.e., predicting another's thoughts), ‘arbitrary inference’ (drawing unwarranted conclusions) and ‘overgeneralization’ (taking one piece of evidence and generalising to other situations) were related to marital conflict. CEs were assessed using the Interpersonal Cognitive Distortions Scale (ICDS; Hamamci & Büyüköztürk, ) and were grouped into three categories: (1) Interpersonal Rejection, (2) Unrealistic Expectations and (3) Interpersonal Misperceptions. Results revealed that having CEs pertaining to unrealistic expectations (‘I need a person around me at all times’) in one's partner was associated with high levels of relationship conflict.…”
Section: Interpersonal Behaviour and Depressionsupporting
confidence: 92%
“…Yapılmış bazı çalışmalar bu fikri destekler niteliktedir. Bu çalışmalarda ilişkilerle ilgili bilişsel çarpıtmalar ile benlik saygısı ve yalnızlık (Turan, 2010), problem çözme becerisi (Ağır, 2007;Güven, 2005), kontrol odağı (Cash, 1984), olumsuz bağlanma stilleri (Stackert & Bursik, 2003), bilişsel çarpıtma, otomatik düşünce ve çatışma eğilimi (Hamamcı & Büyüköztürk, 2004) ve öz-duyarlık (Akın, 2010) arasında ilişki olduğu rapor edilmektedir.…”
Section: İlişkilerle İlgili Bilişsel çArpıtmalarunclassified
“…Since individuals' cognitive distortions cause them to perceive the world in an unrealistic way, this affects them negatively when it comes to evaluating their interpersonal relationships (Hamamcı, 2005). Previous studies seem to support this idea, reporting cognitive distortions in relation to self-esteem and loneliness (Turan, 2010), problem-solving skills (Ağır, 2007;Güven, 2005), locus of control (Cash, 1984), attachment styles (Stackert & Bursik, 2003), automatic thought, tendency to conflict (Hamamcı & Büyüköztürk, 2004), and self-compassion (Akın, 2010).…”
Section: Introduction Cognitive Distortions About Relationshipsmentioning
confidence: 99%
“…These theories suggest that the best way to treat marital conflicts is to focus on these beliefs and change them (Islami ). Therefore, researchers have focused on modifying cognitive distortions and changing the methods of solving problems (Leahy , Hamamci & BuyukOzturk, , Islami ).…”
Section: Introductionmentioning
confidence: 99%